MANAJEMEN LINGKUNGAN BELAJAR ANAK USIA DINI: EFEKTIVITAS TERHADAP PSIKOLOGI BELAJAR ANAK - Umayah; Pertiwi Kamariah Hasis; Farhatin Masruroh; luluk mukaromah; Aushafil Karimah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2025)
Early Childhood Education (PAUD) is the most crucial stage for child development, because at an early age the basic foundations that are very important for cognitive, emotional, social, and physical development are built. Therefore, the management of the learning environment in PAUD has a very crucial role in supporting the learning process and development of children so that children's learning psychology is very effective. In writing this article, the research used a qualitative research method with a library research approach or literature study. The data collection process was carried out through libraries or books, articles, documents related to PAUD learning environment management. Data obtained from data sources were then reduced, presented to obtain conclusions relevant to PAUD learning environment management. The results of the study show that: PAUD learning environment management greatly influences the effectiveness of children's learning psychology. Learning environment management has an impact on children's learning psychology in accordance with Piaget's Constructivism theory and Vygotsky's Sociocultural theory. Where this theory states that children learn through interactions with their environment, in order to adapt the way early childhood learning and can develop child development. This will foster an optimal learning psychology.